EVALUATION AND COMPREHENSIVE COMPARISON OF OCTADECYLAMINE AND STEARAMIDE-BASED SOLID LIPID NANOPARTICLES FOR EFFICIENT GENE DELIVERY - Kirmizitas, Fatma Ceren; Varli, Hanife Sevgi; Tuerkoglu, Nelisa (BEGELL HOUSE INC, 2023)
In recent years various nonviral vector systems have been developed to overcome the disadvantages of viral vectors. Thus, researchers have turned to more secure and easy to reach vector systems. In this study, we have evaluated the gene transfer efficiency of two different nonviral vectors prepared using two lipids: octadecylamine and stearamide. The solid lipid nanoparticles were produced with the emulsion-solvent evaporation method. Particles' mean size, polydispersity index (PDI), and zeta potential values for octadecylamine nanoparticle (ONP) are, respectively, 382.7 nm (+/- 20), 0.4, and 28 mV (+/- 2.03) and for stearamide nanoparticle (SNP) are 276.9 nm (+/- 10.45), 0.3, and 20.4 mV (+/- 4.03), as determined by using Zetasizer via the dynamic light scattering (DLS) method. Morphological characterization of nanoparticles was performed with scanning electron microscope (SEM) and atomic force microscope (AFM). The chemical characterization was performed by Fourier-transform infrared spectroscopy (FTIR). The cytotoxicity of nanoparticles were determined via 3-(4,5-Dimethylthiazol)-2,5-diphenyltetrazolium bromide (MTT) assay with an MCF-7 human breast cancer cell line. The cytotoxicity for both ONP and SNP were calculated over 55%. Also nanoparticles/plasmid DNA conjugates cytotoxicity were determined with no significant toxicity obtained. The transfection efficiency was evaluated by observing green fluorescent protein (GFP) expression in the MCF-7 human breast cancer cell line. The transfection efficiency was 67.5% (+/- 2.3) for ONP, 77.6% (+/- 1.2) for SNP, and 70.7% (+/- 1.4) for commercially available transfection agent.
Keywords: solid lipid nanoparticle; transfection efficiency; gene delivery; CATIONIC LIPIDS; TRANSFECTION; MECHANISM; LIPOFECTION; PROGRESS; THERAPY; STATE; Science & Technology - Other Topics